Pengaruh Stres Kerja Terhadap Kelelahan Kerja Serta Implikasinya Terhadap Kinerja Karyawan Studi Pada Perawat di PKU Muhammadiyah Unit II - Hidayatullah, Rahmad; Handari, Sri (Jurnal Manajemen Bisnis, 2015)
This research aimed to determine the effect of work stress and job burnout implications on employee performance in icu, ugd, and operating room of pku muhammadiyah hospital unit ii. Independent variables used in this study were work stress and job burnout while the dependent variable used is performance.Sample used in this study were nurses at the ICU, UGD, and operating room at pku Muhammadiyah hospital unit II by purposive sampling method. In order to get the number of samples used in this study were 43 respondents and data were analyzed using partial least square with processing aid SmartPLS and data using SPSS 15 software.Thus, results of this study concludes that : 1) Job stress effects positively and significantly toward job burnout. 2) Job burnout takes effect negatively and significantly on performance. 3) Work stress is a significant negative effect on performance. 4) Job Stress take effect negatively and significantly on performance through Job burnout.Keywords: